Effect of an Innovative Science Program on Perceptions of Locus of Control and Satisfaction. - Bar-Tal, Daniel; Leinhardt, Gaea; Bar-Tal, Yaffa (Science Education)
The article presents a study which investigates the effects of an individualized program with goals that are specific to self-direction and coevaluation on students' perceptions of locus of control and satisfaction. In the first phase of the study, pupils' perceptions of locus of control is being evaluated using the Intellectual Achievement Responsibility Questionnaire. In the second phase, pupils were questioned separately with regard to their perceptions of control in a specific class. The subjects were composed of 54 eighth-grade and 26 sixth-grade pupils from a lower middle-class, parochial urban school. Results of the study showed that the perception of locus of control can be affected by the environment.